2010
DOI: 10.1186/cc9372
|View full text |Cite
|
Sign up to set email alerts
|

Is cortisol the key to the pathogenesis of delirium after coronary artery bypass graft surgery?

Abstract: Postoperative delirium is a serious complication of cardiac surgery. However, the pathophysiology of this mental syndrome is largely unknown. Recent findings suggest an association between elevated level of cortisol and postoperative delirium. Further studies should investigate the mechanisms responsible for excessive perioperative cortisol secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…According to recent studies, the most prominent factors contributing to postoperative delirium include comorbid load (atrial fibrillation, prior stroke, anemia, peripheral vascular disease) as well as psychiatric comorbidity such as cognitive impairment and preoperative major depressive disorder (MDD) [5-7]. The pathological association between MDD and postoperative delirium is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent studies, the most prominent factors contributing to postoperative delirium include comorbid load (atrial fibrillation, prior stroke, anemia, peripheral vascular disease) as well as psychiatric comorbidity such as cognitive impairment and preoperative major depressive disorder (MDD) [5-7]. The pathological association between MDD and postoperative delirium is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological association between MDD and postoperative delirium is unclear. These disorders have been proposed to be linked by a greater rise in plasma cortisol, interleukins and abnormalities in amino acids [5,7,8]. However, few studies have attempted to or been able to identify the pathogenesis of delirium following cardiac interventions, although two recent important studies suggest an association with raised postoperative cortisol levels [9,10], whilst Plaschke and colleagues have additionally implicated increased levels of IL-6 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Current thinking implicates cortisol and cytokine abnormalities in cognitive impairment and delirium [7,24,25,26]. Higher cortisol measures have been reported in AD and are associated with poorer memory performance in subjects with cognitive decline [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated risk factors for postoperative delirium, but findings have been heterogeneous. To date, the most consistently reported independent associations with delirium in studies of cardiac surgery include older age, preoperative dementia, nonclassified preexisting cognitive impairment (PreCI; usually both dementia and milder forms of cognitive impairment) and major depressive disorder (MDD) [7,8,9,10]. The other well-established risk factors of delirium include medical conditions such as dehydration, malnutrition, electrolyte or metabolic abnormalities, hypoglycemia, hypoxia, infection, hepatic impairment, renal impairment, cardiac ischemia, multiple medications and alcohol abuse [5,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…3 An elevated level of cortisol was found to be an important factor involved in delirium after coronary artery bypass graft surgery. 7 Another study in individuals age 65 years or older found that S100B is the strongest independent marker. 8 Studies on structural and functional brain imaging, neurotransmitter studies, as well electrophysiologic tests suggest the importance of cerebral cortical and subcortical areas, especially the frontal lobe, subcortical regions, and the right hemisphere.…”
Section: Neuropathologymentioning
confidence: 99%